The Relationship of Digital Literacy, Perception of Internet of Things, and Artificial Intelligence Towards Interest in Entrepreneurship in Generation Z - Monica, Claudia; Andadari, Roos Kities (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
Generation Z is a generation that has IT skills with good mastery of technology. This certainly affects digital literacy in generation Z which is better than the previous generation. Digital literacy is the ability to utilize innovation and data from communication tools in a real and effective way, including for entrepreneurship. Perceptions of IoT and AI can also foster interest in entrepreneurship in generation Z. IoT and AI provide convenience in everyday life, one of which is in entrepreneurship. This study aims to examine the relationship between digital literacy and perceptions of IoT and AI on entrepreneurial interest in generation Z. This study uses a quantitative design with a cross-sectional approach. The population of this study is generation Z with birth years 1996 to 2006. The number of samples in this study was 126 respondents which was determined based on the number of question indicators used in the survey. The data analysis technique used was quantitative with SPSS software. The data analysis tests carried out consisted of instrument tests, classical assumption tests, and multiple linear regression analysis. The results of the study show that digital literacy (sig. 0.00<0.05) and perceptions of IoT and AI (sig 0.00<0.05) have a positive influence on entrepreneurial interest in generation Z. Digital literacy and perceptions of IoT and AI jointly influence entrepreneurial interest in generation Z. Digital literacy and perceptions of IoT and AI provide generation Z with the ability to use information and communication technology and have facilities for technology services for business activities.